Being Black in South African higher education: An intersectional insight - Mlamuli Nkosingphile Hlatshwayo (Acta Academica, 2020)
South African higher education continues to struggle to make sense of the post 2015-2016 student movements in calling for institutional transformation and decolonisation of the academy (Heleta, 2016; Mbembe, 2016; Naicker, 2015). In this paper, I contribute to the emerging body work that looks at transformation and decolonisation in South African higher education. I draw from the American feminist scholar Kimberlé Crenshaw’s theoretical tools of intersectionality and Nat Nakasa and more recently Siseko Kumalo (2018)’s conceptual notion of the “natives of nowhere” to do two things. I firstly use the theoretical tools to map the fragmented and differentiated nature of South African higher education, and the implications this has for decoloniality to emerge. Secondly, I trace the intersectional struggles that Black students and progressive Black academics continue to face in the South African academy, and the discursive struggles operating at different levels, ranging from the alienation; marginality; epistemic violence in the academy; institutional culture(s); an alienating and marginalizing curricula and others that all intersectionally align to produce the postcolonial “natives of nowhere” in the South African academy.